Pengaruh Persepsi Harga, Kualitas Layanan dan Sarana Wisata Terhadap Kepuasan Pengunjung - Juke Sjukriana (Journal of Hospitality and Tourism, 2023)
This study aims to examine and analyze the effect of Perception of Service Quality Prices and Tourism Facilities on Visitor Satisfaction. The object of this study was Tangkuban Perahu visitors located in Bandung, West Java. The sampling technique in this study is Convenience Sampling. Respondents in this study were 150 respondents using the Structural Equation Model (SEM) with Smart-PLS analysis tools. The results of the study that have been obtained after testing the Structural Model / Hypothesis Test (Inner Model) show that the perception of the Price Quality of Service Quality and Tourism Facilities affect the Visitor Satisfaction of Tangkuban Perahu Bandung in West Java. Price Perception Variable has positive and significant effect on Tangkuban Perahu Bandung West Java Visitor Satisfaction. The service quality variable has a positive and significant effect on the satisfaction of Tangkuban Perahu Bandung West Java visitors. And Tourism Facility Variables have a positive and significant effect on the satisfaction of Tangkuban Perahu Bandung West Java visitors.Keyword: Price Perception, Service Quality, Tourist Facilities, Visitor Satisfaction